The Ngaji Duduk Tradition of Banjar Women as a Manifestation of Islam Nusantara: An Analysis of Contemporary Islamic Thought - Agung Nugroho; Zulfa Jamalie (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
This study aims to analyze the tradition of ngaji duduk among Banjar women as a manifestation of Islam Nusantara and to examine its relevance within contemporary Islamic thought. The research focuses on understanding how this local religious tradition functions as a medium for transmitting Islamic values, strengthening women’s religious agency, and preserving indigenous Islamic culture in South Kalimantan. This study employs a qualitative approach using library research methods. Data were collected from books, scientific articles, historical documents, and scholarly works related to Banjar culture, Islamic education, women’s religious participation, Islam Nusantara, and contemporary Islamic thought. The findings reveal that the ngaji duduk tradition represents a living manifestation of Islam Nusantara characterized by moderation, cultural accommodation, social harmony, and contextual religious understanding. Banjar women are not merely recipients of religious knowledge but active agents in maintaining Islamic scholarship, social cohesion, and local religious identity. Furthermore, this tradition reflects contemporary Islamic perspectives that emphasize inclusiveness, contextualization, local wisdom, and the integration of Islamic teachings with socio-cultural realities. The novelty of this study lies in its effort to connect Banjar women’s religious practices with the discourse of Islam Nusantara and contemporary Islamic thought, thereby demonstrating that local traditions can serve as significant instruments for preserving Islamic values amid modern social transformations.